PENGARUH PROMOSI DAN BRAND IMAGE PADA PENINGKATAN NASABAH TABUNGAN EMAS MELALUI KEPUTUSAN MENABUNG DI PEGADAIAN UPS JOHAN PAHLAWAN - Syarief, Mita Meutia (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The decision to save is a very important variable in increasing customers, thus companies must be more strategic in making plans to make customers interested and use the products offered. This research aims to determine the effect of promotion and brand image on increasing customers through the decision to save as a mediator in gold savings products at PT. Johan Pahlawan UPS Pawnshop. The sampling technique used was random sampling with a sample size of 74 respondents. The data used was collected using a questionnaire distributed via Google Form. The data analysis technique used is path analysis to determine the relationship between independent and dependent variables through intervening variables or mediating variables. The results obtained from this research are as follows: 1) promotion has an effect on increasing customers, 2) brand image has an effect on increasing customers, 3) the decision to save has an effect on increasing customers, 4) promotion, brand image, and the decision to save have an effect on increasing customers, 5) promotions influence the increase in customers through the decision to save, and 6) brand image influences the increase in customers through the decision to save. Keywords: Promotion, Brand Image, Increase in Customers, Decision to Save